PENGARUH KUALITAS KOMITE AUDIT, UKURAN PERUSAHAAN, REPUTASI AUDITOR, PERUSAHAAN ANAK TERHADAP KETERLAMBATAN AUDIT PADA PERUSAHAAN MANUFAKTUR - Danang Choirul Umam (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2019)
This study aimed to examine the influence of the Audit Committee, Company Size, Reputation Auditor, a Subsidiary of the Audit Delay. This research was conducted at the company's manufacturing base and chemical industry sectors that exist on the Stock Exchange during the period 2013 - 2015. Based on the method of sample selection, the sample is obtained at the end of the study where 77 of the manufacturing sector in BEI.The analytical methods used are multiple regression analysis. Statistical t-test was performed before analysis of multiple regression equation, in the first phase of testing performed classical assumption of normality, multicollinearity, heteroscedasticity and autocorrelation. Once the data is free from classical assumptions, the next stage is hypothesis testing is done by using the t test to determine the effect of each variable to be partly independent variables.Based on the analysis, it is known that the audit committee, the auditor's reputation and its subsidiaries do not affect the audit delay. While the size of the company negatively affect audit delay. The coefficient of determination that saw the influence of the independent variables used in the study model of the dependent variable was 16.7% while the rest (83.3%) is explained by other variables.